Competitive advantages and strategy options for women entrepreneurship: ICT as integration platform - Fuad, Nurwahida; Bohari, Abdul Manaf (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
In the perspective of world wide marketplace, competitive advantages is the top most issues that facing by entrepreneurs in everywhere at every time. As well as important of competitive advantages to entrepreneurs, women entrepreneurs will face a lot of challenges. In the one hand, competitive advantages will bring themselves into the right way forward and assist them to scan and follow the current change of external and internal environment of business, in order to generate new knowledge to the managers. However, in the one hand, competitive advantages has potential to bring more damage to women entrepreneurs if they are not able to choose the suitable strategy to implemented in the current practice of operation. Furthermore, competitive advantage is anything a firm does especially well compared to rival firms either in international operations or local operations of businesses. As a fundamental of discussion, there are some current trends on competitive advantages issues that faced by women entrepreneurs will analyzed. Then, the paper discussed the competitive advantages forces of women entrepreneurs firms, specifically refers to the model of Porter Five Forces by Michael Porter. Strategy options and it practically implementation within women entrepreneurs firms also discuss with specific focused on the used of Information and Communication Technology (ICT) as integration platform. In the real market environment, ICT is the most cited tools by the researchers to help the women entrepreneurs firms to strengthening their position in the currents trends of market share. Finally, some suggestion was made to guiding women entrepreneurs in adopting ICT as platform to integrating their competitive advantages and strategy choices.